L5-S1 SURVIVAL AFTER INTERBODY FUSION BY LATERAL APPROACH UNTIL L5 IN DEGENERATIVE DISEASE - Silva,Fernando Toni Marcelino da (2019)
ABSTRACT Objectives: Whether or not to include L5-S1 in multiple level lumbar fusions is not yet a consensus in the literature. The option to preserve L5-S1 maintains the mobile segment and the possibility of a natural fit to the sagittal alignment of the lumbar spine. However, a long fusion above L5-S1 may accelerate the degenerative process and an extension to the sacrum may be necessary in the future. In this study, we evaluated the survival of the L5-S1 level after lateral lumbar interbody fusion (LLIF) of 3-4 levels up to L5 and attempted to identify risk factors that could guide the selection of cases. Methods: Retrospective study in a single center. Inclusion: Patients that submitted to interbody fusion (LLIF) from 3-4 levels to L5 due to degenerative spine disease with at least 5 years of follow-up. Exclusion: L5 sacralization or L5-S1 disc ankylosis. We evaluated the reoperation rate including L5-S1 disc. We reviewed the preoperative images regarding coronal Cobb angle, lumbar lordosis, pelvic incidence; distal fractional curve; radiographic classification of DDD (modified by Weiner and Pfirrmann), as well as demographics parameters. These parameters were compared between the case group (reoperated) and the control group. Results: Forty-seven patients were included achieving a success rate of inclusion of 81%; the mean age was 69.1 years, 83% were women, and the mean of operated levels was 3.2. The survival rate of L5-S1 level was 89.6% at 5-year follow-up. No differences were found between the groups regarding the parameter evaluated. Conclusions: The L5-S1 survival rate was 896% after LLIF of 3-4 levels up to L5 at 5-year follow-up. Statistically no risk factors were found to warrant preoperative inclusion of L5-S1. Level of Evidence III; Retrospective Study.